Lb3.254 Greater than tenfold increase in pharyngeal chlamydia trachomatis among gay and bisexual men attending australian sexual health clinics 2010–2016. (8th July 2017) - Templeton, David J; Comninos, Nicholas B; Rutherford, Alison; Goddard, Sian L; Guy, Rebecca; Donovan, Basil; Varma, Rajesh; Callander, Denton
Abstract : Introduction: Gay and bisexual men (GBM) are disproportionately affected by Chlamydia trachomatis (CT). A steady increase in CT notifications has been observed in Australia's most populous state (NSW), with an increasing proportion being pharyngeal CT (PCT) notifications. Our aim was to investigate temporal trends and associated behavioural factors of PCT compared to anogenital CT among GBM attending NSW sexual health clinics. Methods: Clinical data were extracted in early 2017 for the period 2010–2016 from 26 NSW clinics. Positive test yield ("yield") was defined as the proportion of testing occasions where CT was detected. Results: 23, 423 GBM were tested on 84 385 occasions during the 7 year study period to end 2016. Yield of genital testing was 8.8% (95%CI: 8.5–9.0), increasing by 17% over the study period (8.1%–9.5%, p<0.001). Yield of anorectal testing was 7.2% (95%CI: 7.0–7.4), increasing by 23% during the study period (6.0%–7.4%%, p<0.001). Yield of pharyngeal testing was 2.2% (95%CI: 2.1–2.3), increasing by over 1200% from 0.3% in 2010 to 3.7% in 2016 (p<0.001). Of the 8933 positive CT tests (at any anatomical site), 424 (4.8%) occurred without concurrent anogenital CT ("isolated PCT"). The proportion of isolated PCT increased from 2.0% in 2010, to 6.4% in 2015 and 4.4% in 2016 (p<0.001). In 2016, PCT was associated with injecting drug use (p=0.014) and higher numbers of sexual partners (p<0.001), after adjusting for men who reported symptoms or were CT contacts. These factors were the same as those associated with anogenital CT infections. Conclusion: The likelihood of detecting CT among GBM has increased over time with by far the greatest increase in positive test yield occurring in the pharynx. The same factors were associated with CT detection at all sites. Given that most untreated PCT persists on average for 2 years, is readily transmitted to anogenital sites and that one in 20 of all CT infections would be missed, consideration should be given to routine screening of the pharynx in other countries to reduce CT transmission among GBM.